Partisipasi Masyarakat dalam Pemilihan Umum Serentak Tahun 2019 di Kelurahan Ubung Kecamatan Denpasar Utara, Kota Denpasar - Luh Putu Suryani; I Gusti Agung Ayu Diah Aprillia; I Wayan Arthanaya (Jurnal Konstruksi Hukum, 2021)
Election is a series of activities in democratic voting. In this regard, the election is regulated in Law Number 7 of 2017, here it explains how the participation of the people of Ubung Village in the context of participating in the 2019 election process. This study aims to determine the election management system according to Law No. 7 of 2017 and knowing about the implementation of the election in Ubung Village. This type of research is empirical research. This research was carried out by going directly to the research location which was located in the Ubung Village. The results showed that the stages in the people's participation in the kelurahan ubung are: in the election process it can be classified into 3 (three) stages, namely: the preparation stage, the implementation stage, and the evaluation stage. So in this regard here it is said that the phase of people's involvement in the election of the Kelurahan ubung is very enthusiastic because almost 49.41% of the registered voters of the Kelurahan ubung and the Permanent Election list come to the polling stations to exercise their voting rights.